Stable isotope ratios (δ13C and δ15N) and heavy metal levels in macroalgae, sediment, and benthos from the northern parts of Persian Gulf and the Gulf of Oman. (February 2021) - Irandoost, Farnaz; Agah, Homira; Rossi, Loreto; Calizza, Edoardo; Careddu, Giulio; Costantini, Maria Letizia
Abstract: In this investigation, δ 13 C and δ 15 N isotope ratios and heavy metal levels were assessed in macroalgae, sediment samples, and benthic species from northern parts of the Persian Gulf and the Gulf of Oman. The highest δ 15 N values in algal samples (11±0.42), indicative of anthropogenic organic N inputs, were detected in the Sadaf region, whereas the lowest values (3.17 ± 0.12), indicative of anthropogenic inorganic inputs, were detected in the Parvaz region. In addition to sediment quality guidelines (SQGs), contamination factors (CF), enrichment factors (EF), contamination degree (CD), pollution load index (PLI), geo accumulation index (Igeo), and potential ecological risk index (RI) were employed to assess the anthropogenic influence on sediment quality and to describe the sensitivity of the biota to toxic heavy metals. The obtained results demonstrate that the analyzed elements (Mn, Cr, Ni, Pb, Zn, Cu, Co, and V) had no ecological risk in the sampling area. Highlights: δ 15 N in bivalves closely matched those observed in macroalgae. The highest δ 15 N was observed at Sadaf, indicative of anthropogenic organic N inputs. TOC/TN in sediments was less than 10, indicative of marine origin of organic carbon. SBAF showed that accumulation of metals in algae samples was independent of sediments. High EF levels of Cr, Pb and Mg in sediments confirmed their anthropogenic source.